2017 Annual Sustainability Report (Infonavit, 2018)
The Annual Sustainability Report highlights the inter-institutional work and contributions enhancing Infonavit's growth in terms of sustainability, as well as its challenges and opportunities related to its steady growth involving social calling focused on contributing to the well-being of Mexican workers.